Insulating and sheathing materials of electric cables. Common test methods. Methods specific to polyethylene and polypropylene compounds. Tensile strength and elongation at break after pre-conditioning. Wrapping test after thermal ageing in air. Measurement of mass increase. Long-term stability test. Test method for copper-catalysed oxidative degradation Part 4-2, (15th April 2000) - British Standards Institution,
No abstract available